Law of the environment and armed conflict - Hulme, Karen (International library of law and the environment, 2017)
Law of the Environment and Armed Conflict discusses the most important and influential research articles relating to the protection of the environment in armed conflict. This research review plots the trajectory of research on this issue from early weapons impacts and the Vietnam War, to the first major challenge for wartime environmental protections in the Gulf Conflict, liability for harm and possible future directions.